Systemic metabolic reprogramming and microbial dysbiosis in Fabry disease: Multi-omics mechanisms and implications for drug development - Gómez-Cebrián, Nuria; Trull, María Chovi; Gras-Colomer, Elena; Edo Solsona, María Dolores; Poveda Andrés, José Luis; Puchades-Carrasco, Leonor (Frontiers in Pharmacology, 2025)
Current treatments, including enzyme replacement and pharmacological chaperones, have improved disease outcomes but often fail to fully prevent progression or alleviate persistent symptoms, underscoring the need for novel therapeutic strategies. Recent systems biology and multi-omics approaches have revealed consistent and previously underappreciated alterations in systemic metabolism and the gut microbiota in FD. Here, we synthesize evidence from metabolomic, lipidomic, transcriptomic, and metagenomic studies in patients and experimental models, highlighting disturbances in redox balance, mitochondrial function, energy metabolism, and microbiota-derived metabolites such as short-chain fatty acids and tryptophan catabolites. These findings point to new mechanisms underlying gastrointestinal, inflammatory, and metabolic complications in FD, with direct implications for biomarker discovery and drug development. We further discuss the challenges of integrating multi-omics data into clinical research, the value of mechanistic studies in disease models, and the potential for translating omics-derived insights into precision diagnostics and targeted therapies. By framing FD as a systemic disorder of metabolic and microbial dysregulation, this review outlines a roadmap for mechanism-based interventions that extend beyond canonical glycosphingolipid targets.